Housing market spillovers: evidence from an estimated DSGE model - Matteo Iacoviello; Stefano Neri (National Bank of Belgium, 2008)
We study sources and consequences of fluctuations in the housing market. The upward trend in real housing prices of the last 40 years can be explained by slow technological progress in the housing sector. Over the business cycle, housing demand and housing technology shocks explain one-quarter each of the volatility of housing investment and housing prices. Monetary factors explain 20 percent, but they played a bigger role in the housing cycle at the turn of the century. We show that the housing market spillovers are non-negligible, concentrated on consumption rather than business investment, and have become more important over time.
Keywords: E32; E44; E47; R21; R31; 330; Housing; Wealth Eects; Bayesian Estimation; Two-sector Models; Immobilienmarkt; Ländlicher Raum; Gebäudeinstandhaltung; Konjunktur; Vermögenseffekt; USA